Konseling Religius: Suatu Proses Penemuan Makna Hidup Remaja Gagal Menikah - Eni Kuswatun; Maemonah (ILIN Institute, 2021)
The study aims to find out why teens who fail to marry provide religious counseling to find meaning in life. Research is descriptive qualitative the phenomenon is a case study in young people who fail to marry. Data is gathered throught interviews, observation and discussion. Studies have shown that the life meaning of a youth who is undermarried begins with his or her religious counseling at the boarding school in order to give up the sadness he feels over a difficult situation and the hope of changing can change him for the better. By himself following the process of religious counseling in the boarding house marked self acceptance of the problem faced, finding his benefits compared with the previous one. The relization that the issues befell him were god’s enlightened destiny in a better future.